The discourse of neoliberalism : an anatomy of a powerful idea - Springer, Simon (Discourse, power, and society., 2016)
Why should we be worried about neoliberalism if we are not able to fully appreciate its deleterious effects? How can we fully appreciate its intricacies and power without attending to and seeking to potentially reconcile the various critical theorizations of how it actually operates? The Discourse of Neoliberalism offers a critical political economy-meets-poststructuralist perspective on the relationship between neoliberalism and power. By advancing a geographical approach to understanding the discursive formations and material consequences of neoliberalism, the book exposes how processes of neoliberalization are shot through with violence. It argues that reading neoliberalism as a discourse better equips us to understand the power of this variegated economic formation as an expansive process of social-spatial transformation that is intimately bound up with the production of poverty, inequality, and violence across the globe. It illuminates the vital and ongoing power of neoliberalism in order to open up a critical space for thinking through how life beyond neoliberalism might be achieved.